Pelaporan keuangan alokasi dana desa sebagai salah satu akuntabilitas keuangan desa - Sululing, Siswadi (Jurnal Ekonomi, 2017)
This study entitled: "Financial Reporting Village Fund Allocation as One Financial Accountability Village". The formulation of the problem is "Is the village of Buon Financial Reporting Allocation Independent in 2015 in accordance with decree No. Banggai 5 2015 ?. Researcher using secondary data, financial reports Desa Ban Mandiri allocation of funds for Fiscal Year 2015. The purpose of short-term studies to prove whether the allocation of funds financial reporting Desa Ban Mandiri in 2015 in accordance with decree No. Banggai 5 In 2015, while long-term goal of this research is expected to be useful for the development of the science of government accounting, especially financial accounting of the village and as a reference for other researchers who want to examine the same problem. Tests carried out on the basis of the problem formulation wake theory / concept where the alleged causal relationship of each variable has been identified by a clear conceptual framework. For the purpose of the data collection variables operationalized research clearly from the variable / dimensions, concepts, indicators, measurement units, and measurement scale. Data used in this study is a type of secondary data that document the financial statements of the allocation of funds Desa Mandiri Buon Fiscal Year 2015. Once the data are collected then performed a descriptive analysis of financial reports village allocation fund has been made with regard to Banggai Regent Regulation No. 5 2015. The results showed that the financial reporting of the village fund allocation by the government village Buon Mandiri in accordance with decree No. Banggai 5 2015.